Giải pháp phát triển thương hiệu khách sạn PULLMAN HANOI : Giải pháp phát triển thương hiệu khách sạn PULLMAN HANOI / Phạm Hà Châu, Nguyễn Văn Thanh - Phạm, Hà Châu
Giải pháp phát triển thương hiệu khách sạn PULLMAN HANOI